2022
DOI: 10.21608/ejchem.2022.149781.6473
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Reactive Dyes, Part V: Eco-Friendly Approach of Reactive Red 195 Dye Effluents Decolorization Using Geopolymer Cement Based on Metakaolin

Abstract: Our strategy, which we developed a decade ago, aims to reduce pollution rates by treating the water generated from the dyeing process. Here we did the same study but using reactive dyes, by decolorizing red effluent 195 using two different types of geopolymer based on metakaolin. The factors affecting decolorization were studied such as the adsorbent dose, duration, different pH and finally the dose of dye used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…On the adsorption capabilities of the FM geopolymer composite against reactive blue 19 dyeing bath effluent, the impacts of the addition of nano TiO2, adsorbent dose, pH value, and contact time were examined. A certain amount of the adsorbent (0.01-0.15 g) and 50 mL of dyeing bath effluent solution with a concentration of 250 mg/L were combined in a water bath at 140 rpm and 30°C at various contact times and pH levels [40][41][42]. Reactive blue 19 dyeing bath effluent was tested to determine the optimum pH, contact time, and adsorbent dosage that would provide the highest removal efficiency.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…On the adsorption capabilities of the FM geopolymer composite against reactive blue 19 dyeing bath effluent, the impacts of the addition of nano TiO2, adsorbent dose, pH value, and contact time were examined. A certain amount of the adsorbent (0.01-0.15 g) and 50 mL of dyeing bath effluent solution with a concentration of 250 mg/L were combined in a water bath at 140 rpm and 30°C at various contact times and pH levels [40][41][42]. Reactive blue 19 dyeing bath effluent was tested to determine the optimum pH, contact time, and adsorbent dosage that would provide the highest removal efficiency.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…The reactive dyestuff was hydrolyzed by adding a 3 mL/L sodium hydroxide solution (33%) and a 5 g/L sodium carbonate solution, and heating them at 80°C for two hours while stirring. Finally, cooling and neutralisation with diluted sulfuric acid were applied to the hydrolyzed dye [32][33][34]. 1.…”
Section: B-preparation Of Hydrolyzed Reactive Dyementioning
confidence: 99%
“…Elapasery M.A. et al [31][32][33][34] suggested using metakaolin-based geopolymer and slag-based geopolymer cement to eliminate the colour of the reactive dye that is still present in the dyeing bath rather than leaving this hazardous waste untreated. Numerous studies have shown that geopolymers with metakaolin as their primary ingredient are effective adsorbents for a range of water pollutants, including those containing heavy metals and dyes [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Elapasery M.A. et al [30][31][32][33] proposed that metakaolin-based geopolymer cement can be used to remove the color of the reactive dye remaining in the dyeing bath instead of leaving this dangerous waste without treatment.…”
Section: Introductionmentioning
confidence: 99%